Pregnancy as a cause of gastroesophageal reflux after mini-gastric bypass bariatric surgery (MGB-OAGB). A clinical case - V. S. Samoylov; V. V. Novomlinskiy; N. А. Malkina (Акушерство, гинекология и репродукция, 2018)
The number of post-bariatric patients is increasing from year to year; any medical specialist can see consequences and sometimes complications of these interventions. The variety of different scenarios associated with such patients is not well studied. Mini-gastric bypass (MGB-OAGB) is a major type of primary or recurrent bariatric surgery in obese patients. Biliary reflux (BR) is one of the most significant late complications of this operation. An increase in the intra-abdominal pressure during pregnancy can lead to the development of BR with its typical clinical symptoms, which may sometimes puzzle an obstetrician-gynecologist. In these cases, there are limitations in using traditional diagnostic approaches and regular medications for conservative treatment of BR. This report presents a clinical observation on a patient who underwent MGB-OAGB as a recurrent bariatric intervention for her morbid obesity. With no signs of gastroesophageal reflux before surgery, soon after it or in the I trimester of pregnancy, a typical clinical picture of BR developed in the II and III trimesters. A complete relief of the BR symptoms after the childbirth (confirmed by gastro-esophago-scopy) suggested a direct connection between the BR and the increase in intra-abdominal pressure during pregnancy.